«De sangre noble y hábiles costumbres»: etnicidad indígena y gobierno en México Tenochtitlan - Connell, William F. (2016)
This essay will discuss the unusual rise to power of don Bartolomé Cortés y Mendoza Axaycatzin, who was appointed by viceroy Cadereita to serve as governor of Mexico Tenochtitlan in 1636 without mandate from the community. He had previously served as governor in Puebla de los Angeles—the most Spanish city in seventeenth century Mexico, which had no original native communities before the arrival of Europeans. The paper will explore the problem of native jurisdiction at times when tribute collections fell. It will also explore how names can signify political authority. Axayacatzin, Cortés, Bartolomé, and Mendoza all signified political status for Europeans and perhaps were assumed to connote authority and status to Tenochca and other native peoples resident in Mexico Tenochtitlan at a time when the city’s indigenous population was becoming increasingly diverse.